ANALYSIS OF THE COMPETENCE AND PROFESSIONALISM OF THE STATE CIVIL APPARATUS (ASN) IN IMPROVING PUBLIC SERVICES IN THE FIRE AND RESCUE SERVICE - M. Harry Mulya Zein; Sisca Septiani (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2022)
This study aims to analyze and explain the level of competence and professionalism of the State Civil Apparatus (ASN) in improving services at the North Jakarta Fire and Rescue Service. This research uses a qualitative method of collecting data through interviews, observations, and secondary data. The results showed that ASN's competencies include technical, managerial, socio-cultural, and integrity aspects. ASN professionalism involves attitudes, behaviors, and work qualities that reflect dedication, integrity, and responsibility. Education has met the competencies, but training is needed to improve employee professionalism. Public service civil servants at the North Jakarta Fire and Rescue Service are responsive, effective, efficient, and highly quality. An indicator of the success of employee professionalism is seen in the increase in fire and rescue service time. With adequate competence, high professionalism, and quality public services, civil servants in the North Jakarta Fire and Rescue Service can provide optimal services to the community. To achieve this goal, it is recommended to improve education training and implement a code of ethics, transparency, accountability, and efficient management of resources.